The Role of Self Disclosure Against Student Stress During Online Lectures During the Covid-19 Pandemic - Diah Betari Karlinda, Indiani; Andhini, Luh Putu Ratih; Utami, Ni Made Sintya Noviana (Journal of Research and Measurement in Psychology: JPPP, 2022)
The Covid-19 pandemic has forced many state goverments to present learning alternatives in the form of bold learning. However, the alternative clearly has an impact on students' stressful conditions. Understanding stress is knowing the situation experienced or self-disclosure. This study aims to examine the relationship between self-disclosure and student stress while undergoing courageous lectures during the Covid-19 pandemic. The method used is qualitative with a cross sectional design conducted on X University students. The data analysis used is a simple linear regression test. The significance value is 0.048 (ɑ < 0.05) with a B value (regression coefficient) of 0.311 and an R Square value of 0.02. That is, there is a positive relationship of self-disclosure to stress with a contribution of 2%. The picture of student stress is at the moderate level (45.6%) and the picture of self-disclosure is at the moderate level (49.2%). There is a positive relationship between self-disclosure and stress on X student